Determining the amount of Lüders band in niobium microalloyed steel - I. Jandrlić (Metalurgija, 2016)
The article presents the results of measuring the amount of deformation during the formation and propagation of Lüders bands through the deformation zone. The amount of deformation was determined by applying the visioplasticity method with digital image correlation, and analyzing the captured images using the MatchID software package. Results show that during the formation of Lüders bands, the deformation of 0,004 mm/mm was achieved. Furthermore, it was determined that during the propagation of Lüders bands through deformation zone, the sample was deformed in the amount of 0,05 mm/mm.